Investing in Residential Property in Singapore: Misperceptions and Financial Leverage Principles - Ng, Edward H. K. (Institutional Knowledge at Singapore Management University, 1995)
The buoyant residential property market in Singapore is addressed. The economic reasons underlying the recent boom in residential properties is traced, and some of the common misperceptions among property investors are discussed. A set of principles for investing in properties is provided and the implications arising from these principles for the choice of mortgage financing and the type of properties to investing are presented.